2021
DOI: 10.3390/v14010033
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Assessment of Bacteriophage Therapy against Experimental Acinetobacter baumannii Lung Infection

Abstract: Respiratory infections caused by multidrug-resistant Acinetobacter baumannii are difficult to treat and associated with high mortality among critically ill hospitalized patients. Bacteriophages (phages) eliminate pathogens with high host specificity and efficacy. However, the lack of appropriate preclinical experimental models hampers the progress of clinical development of phages as therapeutic agents. Therefore, we tested the efficacy of a purified lytic phage, vB_AbaM_Acibel004, against multidrug-resistant … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…In the context of lung infections with MDR-bacteria, phage therapy is of great interest for treating VAP patients. While recent studies used intratracheal applications [ 74 ] or nebulized phage suspensions [ 7 , 75 , 76 ], here we show that systemic applications of two different phage cocktails are suitable for the dissemination of phages to the lung. The phage cocktails are well-tolerated and do not induce a marked immune response in naïve mice warranting their future evaluation as antibacterial therapeutics.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the context of lung infections with MDR-bacteria, phage therapy is of great interest for treating VAP patients. While recent studies used intratracheal applications [ 74 ] or nebulized phage suspensions [ 7 , 75 , 76 ], here we show that systemic applications of two different phage cocktails are suitable for the dissemination of phages to the lung. The phage cocktails are well-tolerated and do not induce a marked immune response in naïve mice warranting their future evaluation as antibacterial therapeutics.…”
Section: Discussionmentioning
confidence: 54%
“…An increasing number of in vivo studies in animal models [ 7 , 8 , 9 ], as well as human case reports [ 10 , 11 , 12 , 13 , 14 , 15 ], have suggested the efficacy of phage therapy over the past two decades. To date, however, only a few clinical trials of phage therapy have been attempted in humans [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is already data in ABI suggesting the efficacy of phage therapy in animal or in vitro models [195 ▪ ,196 ▪ ,198 ▪ ,209 ▪ –211 ▪ ,212–214,215 ▪ ].…”
Section: What Are the Alternative Treatments For Acinetobacter Bauman...mentioning
confidence: 99%
“…Other studies on the effectiveness of phage therapy in the treatment of respiratory infections with the clinical isolate A. baumannii RUH 2037 in a mouse model and in a human lung tissue model showed that mice, after a single intratracheal administration of the lytic phage vB_AbaM_Acibel004, recovered faster than untreated mice and had a lower bacterial burden in the lungs. The bactericidal effect of the purified phage on A. baumannii after a single dose was also confirmed in an ex vivo human lung infection model [ 29 ]. In 2021, a paper was published presenting the results of phage therapy along with antibiotic therapy in an 88-year-old man who was diagnosed with nosocomial pneumonia caused by carbapenem-resistant A. baumannii .…”
Section: Introductionmentioning
confidence: 95%